Distinguishing severe asthma phenotypes: Role of age at onset and eosinophilic inflammation - Miranda, Christina; Busacker, Ashley; Balzar, Silvana; Trudeau, John; Wenzel, Sally E. (Journal of allergy and clinical immunology, 2004)
Asthma is a heterogeneous process, yet little is understood regarding phenotypes. To determine whether phenotypic differences exist between early-onset, severe asthma as compared with late-onset disease and whether the presence or absence of eosinophilia influences the phenotypes. Cross-sectional analysis of integrated clinical, physiologic, and pathologic data collected from 80 subjects with severe asthma. Subjects were divided into those with asthma onset before age 12 years (n = 50) versus after age 12 (n = 30) and by the presence or absence of lung eosinophils. Subjects with early-onset, severe asthma had significantly more allergen sensitivity (skin test positivity, 98% vs 76%, P < .007) and more allergic symptoms ( P values all ≤ .02) than subjects with late-onset asthma. In contrast, subjects with late-onset asthma had lower lung function ( P values = .05 to .07) than early-onset, despite a shorter ( P < .0001) duration of illness. Both groups had a high degree of general asthma symptoms, but those with persistent eosinophils from either age at onset group had significantly more (multiple P values < .05). Similarly, the presence of eosinophils in either age at onset group was associated with the lowest lung function ( P ≤ .02). Although late-onset asthma was associated with the highest numbers of lung eosinophils ( P < .007), only early-onset severe asthma was associated with a lymphocytic/mast cell inflammatory process. Finally, subjects with late-onset asthma without eosinophils had no subepithelial basement membrane thickening, suggesting a different pathologic process. Differentiating severe asthma by age at onset and presence or absence of eosinophils identifies phenotypes of asthma, which could benefit subsequent genetic and therapeutic studies.